1996
DOI: 10.1002/(sici)1099-1085(199602)10:2<127::aid-hyp354>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Review of methods for the detection and estimation of trends with emphasis on water quality applications

Abstract: Methods for the detection and estimation of trends which are suitable for the type of data sets available from water quality and atmospheric deposition monitoring programmes are considered. Parametric and non-parametric methods which are based on the assumption of monotonic trend and which account for seasonality through blocking on season are described. The topics included are heterogeneity of trend, missing data, covariates, censored data, serial dependence and multivariate extensions. The basis for the non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(59 citation statements)
references
References 55 publications
0
52
0
1
Order By: Relevance
“…Various parametric and nonparametric tests can be used to detect the changes in the time series (e.g., Kendall 1975;Maidment 1993;Esterby 1996;Rao and Hamed 2001;Kundzewicz and Robson 2004;Khaliq et al 2009;Bezak et al 2015a). The nonparametric χ 2 test (Haan 2002) was used in the study to test the hypothesis about a non-uniform rainfall pattern.…”
Section: Methodsmentioning
confidence: 99%
“…Various parametric and nonparametric tests can be used to detect the changes in the time series (e.g., Kendall 1975;Maidment 1993;Esterby 1996;Rao and Hamed 2001;Kundzewicz and Robson 2004;Khaliq et al 2009;Bezak et al 2015a). The nonparametric χ 2 test (Haan 2002) was used in the study to test the hypothesis about a non-uniform rainfall pattern.…”
Section: Methodsmentioning
confidence: 99%
“…This is a critical limitation for my study because SOD has been identified as a significant source of oxygen demand for the Tualatin River (Rounds and Doyle 1997 The determination of long-tetm trends in water quality parameters has received substantial study throughout the last thitiy years from the techniques perspective (Hirsch and Slack 1984;Esterby 1996;Bekele and McFarland 2004) and with reference to case studies (e.g. Smith et al 1987;Lettenmaier et al 1991;Richards and Baker 2002).…”
Section: Innnohiuzedmentioning
confidence: 99%
“…They suggested that changes in cropland management and fertilizer applications are likely causes for this decrease. Trend estimates in water quality are confounded by discontinuous sampling intervals, sample detection limits, seasonality in water quality signals, variability related to discharge, and anthropogenic change in hydrologic systems (Hirsch et al 1991;Esterby 1996). As a result, much of the body of work concerning trend analysis has centered on capturing these sources of variability in order to an·ive at statistically robust estimates of change in water quality.…”
Section: Innnohiuzedmentioning
confidence: 99%
See 1 more Smart Citation
“…Also useful for the detection of trends there are a variety of graphical techniques. For a detailed description of such methods readers may refer, for example, to texts such as Hirsch et al, 1982;Lettenmaier et al, 1982;Hirsch & Slack, 1984;van Belle & Hughes, 1984;Helsel, 1987;Lettenmaier, 1988;Hirsch et al, 1991;McLeod et al, 1991;Esterby, 1993Esterby, , 1996Reckhow et al, 1993;Kundzewicz & Robson (eds), 2000;Hess et al, 2001;Kundzewicz & Robson, 2004;Hesel & Frans, 2006;Visser et al, 2009. Several trend tests have also been described in statistical textbooks (e.g.…”
Section: Introductionmentioning
confidence: 99%